FRI0093 FACTORS ASSOCIATED WITH REFRACTORY RHEUMATOID ARTHRITIS (RRA) ACCORDING TO THREE AVAILABLE DEFINITIONS: TWO CROSS-SECTIONAL ANALYSES IN A LARGE ITALIAN MONOCENTRIC COHORT. (2nd June 2020) - Friso, L.; Ometto, F.; Astorri, D.; Botsios, C.; Doria, A.
Abstract : Background: Three definitions of refractory rheumatoid arthritis (RRA) have been proposed: Buch's (B-RRA), i.e. failure of ≥1 anti-cytokine and ≥1 cell-targeted bDMARD [1]; Kearsley-Fleet's (KF-RRA), i.e. exposure to ≥3 bDMARDs classes [2]; De Hair's (DH-RRA), i.e. signs and/or symptoms of RA activity and failure of ≥1 csDMARD and ≥2 bDMARDs [3]. Objectives: To evaluate the rate of RRA according to the three definitions in a monocentric cohort with two cross-sectional analyses in 2012 and 2019. We investigated also the major determinants of each definition. Secondary objective was to evaluate the most frequent treatments in RRA patients. Methods: Patients affected by RA followed at Padova University Hospital were included at two different time points. In the 2012 cohort patients on bDMARDs on 31 st December 2012 and in the 2019 cohort patients on b/target synthetic DMARDs (tsDMARD) on 1 st March 2019. Factors independently associated with RRA definitions were tested with multivariable regression analysis, including all variables achieving a p<0.10 in the univariate analysis. Results: We included 260 patients in the 2012 cohort and 571 in the 2019 cohort. Rate of RRA in 2012 cohort was: 23 (8.8%) B-RRA, 57 (21.9%) KF-RRA and 12 (4.6%) DH-RRA; rate of RRA in 2019 cohort was: 165 (28.9%) B-RRA, 96 (16.8%) KF-RRA and 57 (10%) DH-RRA. Following multivariate regression analysis, in the 2012 cohort a significant association was found between number of bDMARDs treatment and all RRA definitions [Tab.1]. Also in the 2019 cohort the variable associated with all RRA definitions was the number of bDMARDs treatment [Tab.2]. Both in 2012 and 2019, IL6-inhibitors were more frequently prescribed in RRA patients; instead TNF inhibitors were less frequently prescribed in RRA. Conclusion: Rate of RRA in the 2019 cohort was 10-30% which is higher compared to the 2012 cohort. This might be explained by the fact that RRA definitions are mainly affected by the number of bDMARDs. Thus, an accurate RRA definition should consider not only the number of treatments but also the current disease activity. References: [1]Buch MH. Ann Rheum Dis 2018;77:966–969 [2]Kearsley-Fleet L, et al. Ann Rheum Dis 2018;77:1405–1412 [3]De Hair MJH et al. Rheumatology 2018;57:1135-1144 Disclosure of Interests: LARA FRISO: None declared, Francesca Ometto: None declared, DAVIDE ASTORRI: None declared, Costantino Botsios: None declared, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS